Analisis Kondisi dan Karakteristik Ruang Parkir Pengguna Sepeda Motor (Studi Kasus di Rumah Sakit Dr. R. Soedarsono) - Cahyono, Luqman; Wulandari, Kiki Dwi; Utomo, Agung Prasetyo (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Hospital Dr. R. Soedarsono is the only government-owned hospital and first in the city of Pasuruan, so this hospital is indirectly the main reference for residents. Parking space needs for hospital visitors motorcycle users are influenced by 2 things, among others: 1) Parking land users are indeed hospital visitors aiming for the needs of the hospital, 2) Parking land users are indeed non hospital visitors who deliberately leave their vehicles for purposes other than the hospital. Other needs such as entrusting vehicles to get out of the city, to the office and work in companies outside the city of Pasuruan, etc. This happens because the location of the strategic hospital is on the inter-city public transportation lane, triggering non-hospital visitors to leave their motorbikes. The purpose of this study was to determine the condition of motorcycle user parking and to determine the characteristics of motorcycle users in the hospital. The research data collection method is by recording the number of motorcycle plates that enter and exit complete with time, as well as directly asking the needs of parking visitors. The research was carried out for 7 days / 1 week, whereas in 24 hours of sampling throughout the day starting at 06.00-06.00 WIB. The results of this study show: (1) 3353 vehicles entering parking conditions, there are 2917 visitors parking visitors and 436 non-hospital parking users, (2) the highest volume on Thursday 613 vehicles, (3) the highest accumulation of parking on Thursday at 19.00 - 20.00 as many as 340 vehicles and the average maximum accumulation value of 287 vehicles while there are 267 SRP, it is concluded that the accumulation of parking exceeds the area of the parking space unit, (4) the highest parking duration is vulnerable time 120-180 minutes, (5) the number of parking changes an average 1.79 vehicle / parking lot means that for one parking lot serving more than one vehicle, (6) the parking index is an average of 107.54%, so parking facilities are said to be problematic because ip> 100%. for that it is necessary to increase the area of parking or the creation of new parking spaces with vertical parking (multi-storey parking).